ظروف تأسيس الجبهة الجنوبية للثورة الجزائرية وأبرز قادتها (Rawafid Journal for Research and Studies, 2016)
الملخص:إن الانتصارات التي حققتها الثورة الجزائرية على الصعيدين الداخلي والخارجي، دفعت بالاستعمار الفرنسي لعملية التصعيد في سياسته الجهنمية لخنق الثورة الجزائرية، ويتمثل هذا بقطع كافة مصادر التموين، بالإضافة إلى الاعتماد على مناورات عديدة، لذلك كان لزاما على قيادة الثورة الجزائرية التفكير في استراتيجية محكمة لمجابهة المخططات الاستعمارية الفرنسية، وهذا ما سنتطرق إليه في هذا المقال عن ظروف تأسيس الجبهة الجنوبية وأبرز قادتها. Summary: The internal and external victories achieved by the Algerian revolution had pushed the French colonialism to increase the rigidityand the stringency of their hellish policies in order to stifle the Algerian revolution, and for that raison they cut off all sources of supply and rely on several methods, so, it was incumbent for theleadership of the Algerian revolution to think about a strict strategy to confront the French colonial’s plants; this is what we will discuss about in this article which is about: the circumstances of the foundingof the southern front and its most prominent leaders.